Surveillance of device-associated infection rates and mortality in 3 greek intensive care units - Apostolopoulou, Eleni A.; Raftopoulos, Vasilios; Filntisis, Georgios A.; Kithreotis, Prokopis; Stefanidis, Evagelos; Galanis, Petros; Veldekis, Dimitrios (My University, 2013)
Background: Several studies suggest that device-associated, health care-associated infections (DA-HAIs) affect the quality of care in intensive care units, increasing patients' morbidity and mortality and the costs of patient care. Objectives: To assess the DA-HAIs rates, microbiological profile, antimicrobial resistance, and crude excess mortality in 3 intensive care units in Athens, Greece. Methods: A prospective cohort, active DA-HAI surveillance study was conducted in 3 Greek intensive care units from July 2009 to June 2010. The rates of mechanical ventilator-associated pneumonia (VAP), central catheter-associated bloodstream infection (CLABSI), and catheter-associated urinary tract infection (CAUTI) were calculated along with microbiological profile, antimicrobial resistance, and crude excess mortality. Results: During 6004 days in intensive care, 152 of 294 patients acquired 205 DA-HAIs, an overall rate of 51.7% of patients or 34.1 DA-HAIs per 1000 days (95% CI, 29.3-38.6). The VAP rate was 20 (95% CI, 16.3-23.7) per 1000 ventilator-days, the CLABSI rate was 11.8 (95% CI: 9.2-14.8) per 1000 catheter-days, and the CAUTI rate was 4.2 (95% CI, 2.5-5.9) per 1000 catheter-days. The most frequently isolated pathogen was Acinetobacter baumannii among patients with CLABSI (37.8%) and Candida species among patients with CAUTI (66.7%). Excess mortality was 20.3% for VAP and CLABSI and 32.2% for carbapenem-resistant A baumannii CLABSI. Conclusion: High rates of DA-HAIs, device utilization, and anti -microbial resistance emphasize the need for antimicrobial stewardship, the establishment of an active surveillance program of DA-HAIs, and the implementation of evidence-based preventive strategies. (American Journal of Critical Care. 2013;22:e12-e20).
Keywords: Intensive care units; Patients; Microbial